Early Diagnosis of Chronic Obstructive Pulmonary Disease in Smokers Using Spirometry - Sharmin, Rifat; Rahman, Md Mahbubur; Akter, Shamima (Community Based Medical Journal, 2024)
A cross-sectional, observational study was done in the Pulmonology Department of Combined Military Hospital (CMH) Dhaka Cantonment, Bangladesh, from September 2016 to February 2017, to explore the role of spirometry in the early detection of Chronic Obstructive Pulmonary Disease (COPD) among smokers. A total of 70 participants were selected. After taking the detail history, spirometry and chest x-ray were done. The correlation between smoking and COPD was determined. Among the total respondents 44%, 40% and 15.7% had 10-15, 15-20 and >20 pack-year smoking history respectively. Forced expiratory volume in one second/Forced vital capacity (FEV1/FVC) among these three groups of smokers were found 90%/91%, 77%/89%, and 58.4%/88% respectively. Among the participants, 20% had a change in chest X-ray and 23 (32.85%) of respondents had COPD. Among those 23 participants, 13 (18.57%) suffered from mild, 6 (8.57%) suffered from moderate, 3 (4.28%) suffered from severe, and 1 (1.43%) suffered from a very severe level of airway obstruction. Our results suggest that spirometry can be a valuable tool for the early diagnosis of COPD among smokers. Though it was found as a promising option in a small-scale study, further evaluation is necessary through a population screening to confirm its effectiveness. CBMJ 2024 January: vol. 13 no. 01 P: 53-59